Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.5 - Rationalizing Numerators and Denominators of Radical Expressions - Exercise Set - Page 717: 14



Work Step by Step

$\dfrac{5}{\sqrt[3]{9}}$ Multiply the fraction by $\dfrac{\sqrt[3]{9^{2}}}{\sqrt[3]{9^{2}}}$: $\dfrac{5}{\sqrt[3]{9}}=\dfrac{5}{\sqrt[3]{9}}\cdot\dfrac{\sqrt[3]{9^{2}}}{\sqrt[3]{9^{2}}}=\dfrac{5\sqrt[3]{81}}{\sqrt[3]{9^{3}}}=\dfrac{5\sqrt[3]{81}}{9}=...$ Rewrite the expression as $\dfrac{5\sqrt[3]{27\cdot3}}{9}$ and simplify: $...=\dfrac{5\sqrt[3]{27\cdot3}}{9}=\dfrac{5(3)\sqrt[3]{3}}{9}=\dfrac{5\sqrt[3]{3}}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.